2018
DOI: 10.3389/fpsyt.2017.00298
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Aberrant Connectivity Associated with Neurological Soft Signs in Schizophrenia Patients and Unaffected Relatives

Abstract: Brain connectivity and neurological soft signs (NSS) are reportedly abnormal in schizophrenia and unaffected relatives, suggesting they might be useful neurobiological markers of the illness. NSS are discrete sensorimotor impairments thought to correspond to deviant brain development. Although NSS support the hypothesis that schizophrenia involves disruption in functional circuits involving several hetero modal association areas, little is known about the relationship between NSS and brain connectivity. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 66 publications
2
19
1
Order By: Relevance
“…This result is consistent with two previous studies that employed the same ICA method to investigate rs-fMRI spatial maps and reported decreased functional connectivity within the DMN in patients with schizophrenia 17,18 and thus supports the dysconnection hypothesis 3,4 . The present result of decreased connectivity within the DMN also supplements the inconsistent literature of previous ICA studies that observed both decreases and increases [20][21][22] , only increases 19 as well as no differences in the spatial maps of the DMN at all [23][24][25] . In the context of previous inconclusive findings we would like to emphasize that we included more patients in the reported analysis (N = 35) than previous rs-fMRI studies employing ICA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with two previous studies that employed the same ICA method to investigate rs-fMRI spatial maps and reported decreased functional connectivity within the DMN in patients with schizophrenia 17,18 and thus supports the dysconnection hypothesis 3,4 . The present result of decreased connectivity within the DMN also supplements the inconsistent literature of previous ICA studies that observed both decreases and increases [20][21][22] , only increases 19 as well as no differences in the spatial maps of the DMN at all [23][24][25] . In the context of previous inconclusive findings we would like to emphasize that we included more patients in the reported analysis (N = 35) than previous rs-fMRI studies employing ICA.…”
Section: Discussionsupporting
confidence: 89%
“…Rs-fMRI studies employing different methodological approaches have shown various functional alterations in this DMN in patients diagnosed with schizophrenia 8,11,16 . Studies that applied the data-driven method of ICA to resting-state fMRI data of patients diagnosed with schizophrenia and healthy controls reported mixed functional connectivity results within the spatial maps of the DMN including decreases 17,18 , increases 19 , both increases and decreases [20][21][22] , and no differences [23][24][25] between the groups.…”
mentioning
confidence: 99%
“…We suggest that improvers express, stronger than maintainers, the psychosis endophenotype that is characterized by increased connectivity of DMN ( 55 ). The distinct lack of DMN suppression in our ROP improvers subsample replicates a large body of studies that observed increased connectivity at rest in schizophrenia within the DMN hubs and between DMN hubs and extra-DMN areas ( 55 ).…”
Section: Discussionmentioning
confidence: 88%
“…A negative correlation was found between left caudate connectivity and NSS. The study was limited by small sample size and examiners' bias [ 44 ].…”
Section: Reviewmentioning
confidence: 99%